ChemInform Abstract: Crystal and Electronic Structure of the Lithium‐Rich Silver Silicide Li12Ag1‐xSi4 (x = 0.15). Issue 12 (25th March 2014) - Slabon, Adam; Budnyk, Serhiy; Cuervo‐Reyes, Eduardo; Woerle, Michael; Verel, Rene; Nesper, Reinhard
Abstract The new Zintl phase of title is synthesized from the elements (Nb crucible, 650 °C, 8 d).